An Assessment of Sea Wall Capabilities at Penimbangan Beach in Buleleng Regency - Yanti Dewi, Ni Komang; Aryastana, Putu; Gede Suranata, Putu; Windy Candrayana, Kadek (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2024)
Penimbangan Beach, located in Bakti Seraga Village, Buleleng, has functioned as an area for fishermen to catch fish but has now been changed to become a tourism destination. The coastline of Penimbangan Beach is 803 meters, according to direct measurements with coastal protection sea wall along the shoreline in the field. With the change in function, many traders’ kiosks are now selling on the sea wall, and coastal protection has caused damage. Besides that, wave overtopping often occurs during high tides, causing objects that should be protected by the sea wall to be exposed to wave overtopping. Based on the issues mentioned above, a coastal damage assessment is required, divided into 16 segments, each segment being 50 meters. The results of the coastal damage assessment yielded the scales of Priority C (preferred), Priority D (less prioritized), and Priority E (not prioritized). The result of evaluating the physical condition of all of the sea walls received fairly good results. The performance function of the coastal protection at Penimbangan Beach shows that segments 1-5 have good functional performance, requiring only monitoring of the sea wall. However, segments 6-16 have poor functional performance due to wave overtopping, necessitating a reassessment of the sea wall.